IL-18 production is required for the generation of a Th1 response during experimental chromoblastomycosis - Lucas Golçalves Ferreira; Sandro Rogério de Almeida (PLoS ONE, 2025)
Chromoblastomycosis is a chronic fungal infection characterized by the formation of granulomatous lesions in the skin and subcutaneous tissues that begins after inoculation trauma. The disease is more frequently observed in tropical countries such as Brazil. Important studies have been shown a predominantly cell-mediated immune response during chromoblastomycosis. Results from our laboratory showed that Th1 responses are essential to induce protection during chromoblastomycosis. IL-18 is primarily produced by macrophages and is known to induce the production of IFNγ, a cytokine associated with Th1 cell activation. Once produced, IL-18 acts to promote Th1 cell differentiation and activation. Th1 cells, in turn, secrete cytokines such as IFNγ, which are critical for the elimination of intracellular pathogens, including fungi. IFNγ enhances the fungicidal activity of macrophages, promotes the development of antifungal effector mechanisms, and contributes to the containment of fungal growth. Our results indicate that F. pedrosoi is sensed by the NLRP3 inflammasome, which induces caspase-1 activation and production of IL-18. Moreover, IL-18 plays a crucial role in activating Th1 cells and controlling fungal loads during chromoblastomycosis. Further research into the mechanisms underlying IL-18-mediated immunity may lead to the development of novel therapeutic approaches for the treatment of this chronic fungal infection.